The role of biotechnology in animal agriculture to address poverty in Africa: The need for appropriate policies - Nyange, N.E.; Kingamkono, R.R. (TSAP and ILRI, 2006)
Livestock production currently accounts for about 30% of the gross value of agricultural production in Africa. Seventy per cent of the rural poor in Africa own livestock, including pastoralists living in arid and semi-arid zones. Of these, over 200 million rely on their livestock for income (sales of milk, meat and skins) and manure for growing crop. The livestock sector in Africa, characterised by low productivity, is struggling to keep up with the demand for food from animal sources by the expanding human population. Conventional methods of livestock improvement and agricultural research and development have in the past served the purpose of increasing livestock productivity. However, these options can no longer sustain production hence new intensive techniques including biotechnology are now required to augment productivity.